Crystal Structure and Salinity of Sea Ice in Hebron Fiord and Vicinity, Labrador - Gow,Anthony J. (1987)
In this report we present results of measurements of the crystalline structure and salinity characteristics of sea ice in Hebron Fiord and vicinity, Labrador. Structurally, the fiord ice was entirely first year and composed predominantly of congelation, columnar-type crystals. At most of the sampling sites the ice exhibited moderately to strongly aligned c-axes consistent with the inferred direction of near surface currents in the fiord. Generally diminished values of bulk salinity at five separate locations reflect the warm ice conditions encountered at the time of sampling (late May) and the effect of meltwater flushing in promoting loss of brine, vertically, from the ice sheet. Observations outside Hebron Fiord indicated the presence of only minor amounts of multiyear ice during the latter part of May.